Development Of A Fiber Optic Three-Dimentional Vibration Measuring System. - M. Rehman, M. Rehman; Arshad, M. Rizal; Mohammad, Mohammad Ariff (2008)

(untitled)
This paper deals with the development of a three dimensional vibration measuring system. It consists of three units of the basic sensor which are connected in such a way that each will sense the vibrations in the respective axis.